Frequency of Correct Fetal Weight Estimation by Clinical and Ultrasound Methods in Pregnant Women - Inbisaat Anum, Syeda Sahar Zahra, Sapna Kumari, Anum Wahid, Umber Arooj Tahir, Asim Iqbal Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of correct fetal weight estimation by clinical and ultrasound methods in pregnant women. Study Design: A cross-sectional study. Place and Duration: Department of Obstetrics and Gynaecology, Nishtar Hospital Multan, From February 2021 to July 2022. Methodology: A total of 383 women with singleton pregnancy, gestational age between 37 to 40 weeks and who underwent labor induction or elective cesarean section were included. Fetal weight estimation was done by clinical and ultrasound methods in pregnant women. Following delivery, “actual birth weight” of neonate was measured and data recorded in the shape of correct fetal weight estimation by both studied methods. Results: In a total of 383 women, the mean age was 29.50±2.22 years ranging between 18-35 years while the mean gestational age was 38.09±0.91 weeks. The mean mother’s weight was 70.19±10.56 kg, mean clinical weight estimation 3127.03±561.38 grams, mean ultrasound weight estimation 3137.25±658.05 grams and mean actual weight was 3157.63±648.33 grams. Correct clinical weight estimation was reported in 49.6% cases while correct ultrasound weight estimation was noted in 80.9%. Practical Implications: Accuracy in fetal weight estimation can be achieved by applying Dare’s method in the clinical setting. Conclusion: Fetal weight estimation adopting Dare's formula was found to be comparable to ultrasound estimation for the prediction of actual birth weight within 10%. Keywords: Fetal weight, gestational age, singleton, ultrasound.